(untitled) (Revista de Psicología, 2025)
Right Wing Authoritarianism is a construct that has been widely studied due to the adequate applicability demonstrated by the scale proposed by Altemeyer. Although this construct has been investigated in Argentina, there are no studies yet that systematically review the existing literature on this topic. As a result, this article aims to conduct a review of the studies published on Right-Wing Authoritarianism in Argentina. For this, a search was carried out in the databases of BASE, LA Referencia, Redalyc, Scielo, and manually in Google Scholar. The results demonstrate a total of 23 investigations that use scales to measure Right Wing Authoritarianism with different variables from 2010 to February 2023. 52% of the sample was made up of university students, 36% was made up of adults and 9% of the selection was made up of a sample of boys and girls. A tendency was found to measure the construct about Orientation towards Social Dominance and different scales that measure prejudice towards different minorities. This work offers a synthetic summary of the samples, methods, and results of each one. For this reason, the present systematic review allows the understanding of right-wing authoritarianism in Argentina context, creating understanding with the constructs that are related to and the sociopolitical context.